ETosis in tambaqui Colossoma macropomum: A programmed cell death pathway and approach of leukocytes immune response - Gallani, Sílvia Umeda; Valladão, Gustavo Moraes Ramos; Alves, Lindomar de Oliveira [UNESP]; Jesus, Raphael Barbetta de [UNESP]; Kotzent, Suzana [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Wiegertjes, Geert; Pilarski, Fabiana [UNESP] (Elsevier, 2021)
Tambaqui Colossoma macropomum is the most cultivated native fish in South America and Aeromonas hydrophila is one of the main bacteria infecting tropical fish. Despite the economic importance of this round fish, to date, there has been a paucity of investigations into haematological changes in tambaqui. In this study, detailed blood analyses (0 h, 6 h, 24 h, 7 d and 14 d) following intraperitoneal challenge with A. hydrophila were performed. After analysing the results, there was a suspicion of a novel cell death mechanism via extracellular traps (ETosis) in tambaqui. The search for ETosis was based on differential interference contrast (DIC) microscopy and scanning electron microscopy (SEM) assays through application of an adapted protocol applying co-incubation of leukocytes with A. hydrophila. The cells were investigated at: 0 h (control), 4 h and 7 h after incubation. The complete haemogram profile showed an uncommon severe leukopenia in early phases of infection (6 h, p < 0.001 and ≤ 0.05), due to significant decreases in the three main leukocytes: lymphocytes (6 h, p ≤ 0.001), monocytes (6 h, p ≤ 0.05) and neutrophils (6 h and 24 h, p ≤ 0.01 and p ≤ 0.05). Leucocytosis and lymphocytosis (p ≤ 0.01) were ascertained only 7 days post-infection. Through DIC and SEM, we discovered that leukocyte suicide exposed the nuclear contents between 4 and 7 h after stimuli with bacteria. The leukogram profile associated with DIC and SEM analyses suggested that tambaqui leukocytes underwent a programmed death (ETosis) in order to expose chromatin and granule proteins as a trap to bind and then kill bacteria; thus, preventing A. hydrophila from spreading and resulting in leukopenia during the early phase of bacterial infection. In this paper, we presume that ETosis is one of the last resources for tambaqui to contain the infection, and after this leukocyte strategy, a high number of phagocytic cells are produced and released into the peripheral circulation.
Keywords: Aeromonas; Aquaculture; Extracellular trap; Hemorrhagic septicemia; Native fish; NETosis